Proceedings of the 29th Annual ACM Symposium on Applied Computing 2014
DOI: 10.1145/2554850.2555079
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of open-source software developer's commit behavior

Abstract: Commit is an important operation of revision control for opensource software (OSS). Recent research has been pursued to explore the statistical laws of such an operation, but few of those papers conduct empirical investigations on commit interval. In this paper, we investigated the dynamics of software developers' collective commit behavior in terms of the distribution of commit intervals, and found that the data sets of project-level and filelevel collective commit interval within both the lifecycle and each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Such developers are common in utility-oriented FLOSS which doesn't have an independent community associated with it, such as the Linux system excluding the kernel. Ma et al [75] JBossAS, Apache Geronimo, and JOnAS Some developers took several months off between commits. The median commit interval for inactive committers was 2.4 days, compared to 0.08 days for active committers.…”
Section: Koch Andmentioning
confidence: 99%
“…Such developers are common in utility-oriented FLOSS which doesn't have an independent community associated with it, such as the Linux system excluding the kernel. Ma et al [75] JBossAS, Apache Geronimo, and JOnAS Some developers took several months off between commits. The median commit interval for inactive committers was 2.4 days, compared to 0.08 days for active committers.…”
Section: Koch Andmentioning
confidence: 99%
“…The authors also found that commits follow power laws, with large bursts and long tails. Power laws were again found in 4 Apache projects, when analysing the time interval between commits and files committed [35].…”
Section: Applicability Of Traditional Effort Estimation Techniques To...mentioning
confidence: 82%
“…The authors also found that commits follow power laws, with large bursts and long tails. Power laws were again found in 4 Apache projects, when analysing the time interval between commits and files committed (Ma et al 2014). Mockus and Votta (2000) showed that, out of nearly 400 programmers in the Apache project, the 15 most productive ones contributed 88 percent of the total lines of code (LOC).…”
Section: Applicability Of Traditional Effort Estimation Techniques To...mentioning
confidence: 95%